2008
DOI: 10.1016/j.jvs.2007.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary outcomes after superficial femoral artery angioplasty and stenting: The influence of TASC classification and runoff score

Abstract: Self-expanding stents produce acceptable outcomes for treatment of SFA disease. Poorer patency rates are associated with TASC D lesions and poor initial runoff score; HTN was associated with improved patency rates. Stent occlusion and in-stent stenosis were not entirely benign; one-third of patients had deterioration of their tibial artery runoff. Future studies of SFA interventions need to stratify TASC classification and runoff score. Further evaluation of the long-term effects of SFA stenting on tibial runo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
101
3
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 28 publications
5
101
3
2
Order By: Relevance
“…Status of distal run-off also has been adversely associated with SFA patency following EVT. 9 Even though distal run-off was not a determinant for SFA stent patency in the J-SMART study, caution should be exercised when using SFA stenting in very heavily calcified lesions or in patients with very poor or no outflow vessels. Additionally, the authors mention that factors such as absence of cilostazol administration, female gender, younger age and CTO were independent predictors of restenosis.…”
Section: When Should a Stent Be Deployed?mentioning
confidence: 85%
“…Status of distal run-off also has been adversely associated with SFA patency following EVT. 9 Even though distal run-off was not a determinant for SFA stent patency in the J-SMART study, caution should be exercised when using SFA stenting in very heavily calcified lesions or in patients with very poor or no outflow vessels. Additionally, the authors mention that factors such as absence of cilostazol administration, female gender, younger age and CTO were independent predictors of restenosis.…”
Section: When Should a Stent Be Deployed?mentioning
confidence: 85%
“…11 Poor arterial runoff is associated with a higher risk of EV failure, and in these cases, it is necessary to perform multiple and assisted procedures to obtain a good midterm patency rate. 3 Ihnat et al 3 reported a worsening in the runoff score in 35% of TASC D patients who previously underwent EV with stent occlusion and in-stent restenosis, and for this reason, the authors proposed to perform no more than 2 EV attempts to revascularize a leg, and they advised conversion to OS to preserve a distal arterial bed suitable for direct reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…A presença de diabetes melito, leito distal ruim, insuficiência renal, longas lesões oclusivas e isquemia crítica é citada, na literatura, como relacionada à diminuição da perviedade a médio e longo prazo 1,2,6,[20][21][22][23] , enquanto outros não encontraram uma relação precisa 19 . Nossos achados mostraram que somente o diabetes melito e um leito distal pobre (ausên-cia de artéria infrapoplítea pérvia) influenciaram no resultado em 1 ano de acompanhamento.…”
Section: Discussionunclassified
“…Por outro lado, observamos que a extensão das lesões não foi fator determinante para um pior resultado, talvez explicado pelo fato de que a maioria do pacientes de nossa casuística era portadora de isquemia crítica, certamente com lesões extensas e multissegmentares (76%), contrastando com diversos estudos em que há uma maior taxa de claudicantes, em torno de 60% 2,6,20,24,25 .…”
Section: Discussionunclassified